Government pharmaceutical pricing strategies in the Asia-Pacific region: an overview - Naina R. Verghese; Jon Barrenetxea; Yukti Bhargava; Sagun Agrawal; Eric Andrew Finkelstein (Journal of Market Access & Health Policy)
Background and objectives: Governments in Asia Pacific (APAC) are increasingly using pharmaceutical pricing strategies to contain rising healthcare costs. The objective of this narrative review is to discuss formal pricing strategies for reimbursed prescription medication in APAC, supported by relevant examples of implementation differences across countries. In the discussion section, we examine key advantages and disadvantages of each strategy. Methods: A narrative review of the peer-reviewed and grey literature was undertaken to retrieve information, including strategy definitions, practising countries, country-specific implementation considerations, and merits and demerits of each strategy. Results: Seven strategies (Internal Reference Pricing, External Reference Pricing, Special Pricing Agreements, Pharmacoeconomic Evaluation, Cost plus pricing, Price Maintenance Premium, and Tendering and negotiations) were identified as most commonly practised in APAC through the review process. Most countries use multiple strategies that differ in how they are implemented. Conclusion: APAC countries use multiple strategies simultaneously with varying implementation methods, including different formulae and sub-types of medication that a strategy applies to, whether the strategy is a mandate or guideline, and the extent of negotiations and transparency. Strategies are instituted partly with the aim of cost containment, and may also promote price stability, innovation, and increased access in the short and longer term. Abbreviations: APAC - Asia Pacific; WHO - World Health Organisation; IRP - Internal Reference Pricing; ERP - External Reference Pricing; SPA - Special Pricing Agreement; MES - Managed Entry Scheme; PVA - Price-Volume Agreement; RSA - Risk Sharing Agreement; NHIS - National Health Insurance System; PE - Pharmacoeconomic Evaluation; CEA - Cost-Effectiveness Analysis; QALY - Quality-adjusted Life Year; BIA - Budget Impact Analysis; PMP - Price Maintenance Premium; R&D - Research & Development